American-Burkina Faso Political Satire in YouTube Animation Shorts @GlobalPresidents001: Barthes' Semiotics - Aflaha Darajati; Gufron Gufron (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to describe the political satire represented in a short animation on the YouTube channel @GlobalPresidents001, uploaded on September 10, 2025, with a duration of approximately five seconds. The analysis was conducted using Roland Barthes' semiotics, which covers three levels of meaning, namely denotation, connotation, and myth. Data was obtained through observation of visual elements, character expressions, symbols, and visual flow in the animation. Data analysis followed Miles and Huberman's interactive model, which consists of data reduction, data presentation, and conclusion drawing. The results of the study were then linked to a number of previous studies and current phenomena developing in the media related to political relations between the United States and Burkina Faso. Validation was carried out through expert triangulation, peer discussion, and increased analytical rigor to ensure the reliability of the interpretation. The findings show that the animation presents a critique of the manipulative dynamics of political relations. The United States is depicted in a lower physical position to show a strategy of humbling itself for certain political interests. The actions of the American character, who takes Burkina Faso's money pump and then runs away, represent economic exploitation, power imbalance, and irresponsibility in the political cooperation process.